Pengaruh Career Stage, Tenure dan Expectancy yang Dimediasi oleh Pengembangan Karir terhadap Kepuasan Kerja Pegawai Negeri Sipil di Polrestabes Semarang - Qristin Violinda; Alfionita Cindy Shelena; Bayu Kurniawan (Jurnal Dinamika Ekonomi dan Bisnis, 2023)
This study aims to examine the effect of career stage, tenure and expectancy mediated by career development on job satisfaction of Civil Servants at Semarang Polrestabes. This type of research uses quantitative research and uses PLS-SEM data analysis techniques with the help of SmartPLS 3.0 software. The sample used was 99 respondents of Semarang Polrestabes. The results showed that: (1) Career stage has no effect on job satisfaction. (2) Tenure has a positive and significant effect on job satisfaction. (3) Expectancy has no effect on job satisfaction. (4) Career development has a positive and significant effect on job satisfaction. (5) Career stage has no effect on career development. (6) Tenure has a positive and significant effect on career development. (7) Expectancy has a positive and significant effect on career development. (8) Career development does not mediate the career stage against job satisfaction. (9) Career development does not mediate tenure against job satisfaction. (10) Career development mediates expectancy towards job satisfaction